Computer method for predicting the secondary structure of single-stranded RNA. - Studnicka, G M (1978)
We present a computer method utilizing published values for base pairing energies to compute the most energetically favorable secondary structure of an RNA from its primary nucleotide sequence. After listing all possible double-helical regions, every pair of mutally incompatible regions (whose nucleotides overlap) is examined to determine whether parts of those two regions can be combined by branch migration to form a pair of compatible new subregions which together are more stable than either of the original regions separately. These subregions are added to the list of base pairing regions which will compete to form the best overall structure. Then, a 'hyperstructure matrix' is generated, containing the unique topological relationship between every pair of regions. We have shown that the best structure can be chosen directly from this matrix, without the necessity of creating and examing every possible secondary structure. We have included the results from our solution of the 5S rRNA of the cyanobacterium Anacystis nidulans as an example of our program's capabilities.